2021
DOI: 10.1109/jproc.2021.3126493
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Utilization of Excitation Information of Speech: A Review

Abstract: | Speech production can be regarded as a process where a time-varying vocal tract system (filter) is excited by a time-varying excitation. In addition to its linguistic message, the speech signal also carries information about, for example, the gender and age of the speaker. Moreover, the speech signal includes acoustical cues about several speaker traits, such as the emotional state and the state of health of the speaker. In order to understand the production of these acoustical cues by the human speech produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 268 publications
0
10
0
Order By: Relevance
“…The assumed signal model for this measurement is a variant of the sinusoidal model (McAulay and Quatieri, 1986). We need to explore pitch extractors assuming the other signal models, especially excitation-based models (Kadiri et al, 2021). We also need to explore relations to deep-learning-based pitch extractors.…”
Section: Discussionmentioning
confidence: 99%
“…The assumed signal model for this measurement is a variant of the sinusoidal model (McAulay and Quatieri, 1986). We need to explore pitch extractors assuming the other signal models, especially excitation-based models (Kadiri et al, 2021). We also need to explore relations to deep-learning-based pitch extractors.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to understand the acoustic cues that describe the detailed speaker characteristics, including different voice qualities and emotions. Then, utilize this information to identify the speaker [12]. Hence, it is required to capture the features describing excitation and the vocal filter in speech production.…”
Section: Rationale Behind Using Excitation Features In Speaker Identi...mentioning
confidence: 99%
“…Thus, excitation features provide supportive information to the frequently used vocal tract features of various speakers. The different methods are well established to describe the vocal tract filter, but the researchers showed less interest in excitation features [12]. The study of [13] demonstrated the methods to capture the excitation features effectively and mentioned the future scope to combine excitation and vocal tract features.…”
Section: Rationale Behind Using Excitation Features In Speaker Identi...mentioning
confidence: 99%
See 2 more Smart Citations